The Analysis Study of Characteristics and Effectiveness of Postoperative Rehabilitation Strategies in Ankle Fractures: A Comprehensive Systematic Review - Jatniko Fadhilah; Hedaya Pancar Pangestu (The International Journal of Medical Science and Health Research, 2024)
Background: Rehabilitation after ankle fracture surgery is critical for optimizing functional recovery. This systematic review explores various post-surgical rehabilitation strategies, including weight-bearing protocols, compression therapy, manual therapy, and active controlled motion, focusing on their efficacy in improving patient outcomes. Methods: A systematic review was conducted using seven randomized controlled trials and one retrospective analysis. Studies were assessed for interventions such as early versus delayed weight-bearing, compression stockings, manual therapy, active controlled motion, and ankle supports. Key outcomes included functional scores (OMAS, AOFAS), quality of life measures, range of motion, and return-to-activity timelines. Results: Early weight-bearing was associated with better functional recovery and earlier return to work, while active controlled motion improved range of motion and patient-reported outcomes. Compression therapy effectively reduced swelling and enhanced functional outcomes, but manual therapy showed limited benefits. Ankle supports, such as walker boots and stirrup braces, reduced pain and improved gait parameters compared to Tubigrip. Overall, no significant increase in complications was observed with early mobilization strategies. Conclusion: Individualized rehabilitation plans incorporating early mobilization, compression therapy, and supportive devices can optimize functional recovery after ankle fracture surgery. Future research should focus on long-term outcomes and cost-effectiveness of these strategies.